ADSORPSI ION FOSFAT DALAM AIR TAWAR DAN AIR LAUT MENGGUNAKAN ZEOLIT ALAM KOMERSIAL TERLAPISI OKSIDA BESI - , Suratno, Dr. Eko Sugiharto, DEA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Modified commercial natural zeolite with a coating method of iron oxide has been conducted by hydrolysis of Fe3+ solution and NaOH. The modified zeolite was characterized using X-ray diffraction (XRD), while functional groups were identified by infra-red spectrophotometer (IR). The modified zeolite was used to adsorb phosphate ion from the solution using comparator adsorbent of Rowapos (Î²-FeOOH granular). The observed adsorption parameters were pH, contact time, adsorbent mass, phosphate ion concentration and solution types. The result of X-ray diffraction showed 3 major peaks in diffractogram in the diffraction angle (2Î¸) of 22.3411Â°, 27.8800Â° and 9.9150Â° which correspond to d values 3.9761, 3.1975 and 8.91378 Ã, respectively, indicated that the natural zeolite was clinoptilolite type material. The adsorption process of phosphate ion had the highest adsorption percentage (88.6%) occurred at pH 3.02 with a mass of 300 mg adsorbent, initial solution concentration of 2.5 mg.L-1 and contact time of 120 min. The adsorption process of phosphate ion in freshwater was in accordance with kinetic equation pseudo-second-order (Ho) with the k2 value for ZM was 25.96 g.mg-1.min-1 and for Rowaphos was 14.68 g.mg-1.min-1 with adsorption capacities of 0.69 mg.g-1for ZM and 0.87 mg.g-1 for Rowaphos. The adsorption of phosphate ion in saltwater followed kinetic equation pseudo-first- order (Lagergren) with the k1 value for ZM was 0.0051 min-1 and for Rowaphos is 0.0421 min-1 with adsorption capacities of 0.21 mg.g-1 for ZM and 0.91 mg.g-1 for Rowaphos. Phosphate ion adsorption process by ZM and Rowaphos both in freshwater and saltwater was dominated by physisorption with the mean free energy (ED) value < 8 kJ.mol-1 and heat sorption (B) dan ÎG values are < 20 kJ.mol-1.